Monitoring the Occurrence of Alarms in High Flow Nasal Cannula (HNFC) Using IoT-Based Thinger.io Platform for COVID-19 Isolation Room - Sapty Taurisita Fauziah; Muhammad Ridha Mak'ruf; Andjar Pudji; Levana Forra Wakidi; Faraz Masood (Jurnal Teknokes, 2023)
Covid-19 has become a virus that has become a world pandemic and this virus has caused mass deaths because medical personnel have difficulty treating patients when oxygen levels in the blood have fallen to critical levels. HFNC (High Flow Nasal Cannula) is a method of administering additional oxygen to patients with acute respiratory failure. The use of HFNC in recent years has been highly recommended as a solution to provide supplemental oxygen to patients. Administration of HFNC to COVID-19 patients begins at a flow range of 30-60 LPM.Unfortunately, HFNC, which used to exist, can only be monitored manually, resulting in the transmission of HFNC-produced aerosols between patients and staff. So this study aims to analyze errors in HFNC that cause a decrease in flow to HFNC using a flow sensor as a sensor to detect leaks or other flow errors from the HFNC output hose and monitor if there is a blockage through IoT in the form of notifications.This research method uses the Pre-experimental with the After Only Design type. In this design, the researcher only used one group of subjects and only looked at the results without measuring and knowing the initial conditions, but there was already a comparison group. The independent variable in this study was the HFNC error condition. While the dependent variable in this study is the data flow read by the sensor, where IoT notifications and device status show error leaks. The sensors used in this research are MPX5700GP pressure sensors and SEN0343 Differential Pressure sensors as flow sensors. The benefit of this research is that in addition to reducing the burden on medical staff in handling Covid-19 patients, it can also minimize transmission between staff and patients caused by high aerosol production by this HFNC device, this is because HFNC device alarm monitoring can be monitored in the nurse's room via internet technology. In conclusion, to obtain maximum benefits from this research, it is necessary to select a sensor that truly has a high enough resistance to humidity produced by this HFNC humidifier's water vapor.